Voltage-gated sodium channel function and expression in injured and uninjured rat dorsal root ganglia neurons. (1st February 2016) - Yin, Ruoyuan; Liu, Dong; Chhoa, Mark; Li, Chi-Ming; Luo, Yi; Zhang, Maosheng; Lehto, Sonya G.; Immke, David C.; Moyer, Bryan D.
Abstract : The nine members of the voltage-gated sodium channel (Nav) family mediate inward sodium currents that depolarize neurons and lead to action potential firing. Increased Nav expression and function in sensory ganglia may drive ectopic action potentials and result in neuropathic pain. Using patch-clamp electrophysiology and molecular biology techniques, experiments were performed to elucidate the contribution of Nav channels to sodium currents in rat dorsal root ganglion (DRG) neurons following the L5/L6 spinal nerve ligation (SNL) model of neuropathic pain. The abundance of DRG neurons with fast, tetrodotoxin sensitive (TTX-S) currents was seven-fold higher whereas the abundance of DRG neurons with slow, tetrodotoxin resistant (TTX-R) currents was nearly thirty-fold lower when comparing ipsilateral (injured) to contralateral (uninjured) neurons. TTX-S currents were elevated in larger neurons while TTX-R currents were reduced in both small and large neurons. Among Nav transcripts encoding TTX-R channels, Scn10a (Nav1.8) and Scn11a (Nav1.9) expression was twenty- to thirty-fold lower, while among Nav transcripts encoding TTX-S channels, Scn3a (Nav1.3) expression was four-fold higher in injured compared to uninjured DRG by qRT-PCR analysis. In summary, the SNL model of neuropathic pain induced a phenotypic switch in Nav expression from TTX-R to TTX-S channels in injured DRG neurons. Transcriptional reprogramming of Nav genes may drive ectopic action potential firing and contribute to neuropathic pain.